A reply to John Barry. Issue 3 (1st September 2019) - Baker, Stephen
Abstract : In his analysis of the loyalist flag protests of 2012, John Barry finds within them the potential for a civic, progressive politics beyond ethnic grievance; a post-conflict politics that need not be post-political; an agonistic politics of struggle and contestation that need not be violent. As a means to achieve this, John defends the need for single-identity/internal conversations within loyalism. In my reply, I am broadly supportive, but I suggest that such conversations cannot take for granted the continuation of the constitutional status quo.